Remembering the Forgotten War : The Enduring Legacies of the U.S.-Mexican War - Van Wagenen, Michael (Book collections on Project MUSE., 2012)
"This book answers the deeper question of how remembrance of the U.S.-Mexican War has shaped the complex relationship between these former enemies now turned friends. The distant violence becomes a new lens through which to view today's rivalries and resentments"--Page 7.